Fu’s subcutaneous needling for knee osteoarthritis: a systematic review and meta-analysis - Xiaohu Zhao; Jingxuan Liu; Dake Li; Shangkun Si; Xuanhe Tian; Deke Zhang; Ping Jiang; Ping Jiang (Frontiers in Medicine, 2025)
BackgroundAcupuncture has been listed as an alternative treatment in several knee osteoarthritis (KOA) international guidelines. Fu’s subcutaneous needling (FSN), as a novel acupuncture therapy, has shown greater potential for treating KOA. The objective of this systematic review is to compare the efficacy and safety of FSN to routine acupuncture therapy (RAT) for KOA.MethodsChina National Knowledge Infrastructure, VIP, China Biomedical Literature Database, Wanfang Medical, Embase, PubMed, Ovid, and the Cochrane Library were searched from inception to March 2025, and randomized controlled trials on FSN for KOA were included. The primary outcomes were total efficacy rate, Visual Analog Scale (VAS) pain scores and Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores. Literature quality was assessed using Cochrane risk-of-bias tool 1.0. Heterogeneity among trials was assessed using the Cochrane Q test and I2 values, determining model selection (fixed/random effects). The meta-analyses of included studies used odds ratios and mean differences when appropriate, along with significance threshold α = 0.1. The evidence was evaluated by the GRADE guideline. The PROSPERO International Prospective Register of Systematic Reviews received this research for registration (CRD42024595903).ResultsA total of 14 studies were included (1,186 patients, with 594 in FSN group and 592 in RAT group). Primary outcomes: The total efficacy rate of the FSN group was significantly higher than that of the RAT group [OR = 3.83, 95% CI (2.36, 6.91), p < 0.01, n = 10, 470/467 participants]. FSN also demonstrated greater effectiveness in reducing VAS pain scores [MD = −1.44, 95% CI (−1.62, −1.26), p < 0.01, n = 6, 205/206 participants] and WOMAC scores [MD = −6.07, 95% CI (−8.16, −3.97), p < 0.01, n = 5, 160/161 participants]. Secondary outcomes: FSN group showed a greater reduction in inflammatory cytokines: IL-6 [MD = −1.50 ng/mL, 95% CI (−1.55, −1.46), p < 0.01, n = 4, 180/180 participants], TNF-α [MD = −2.26 pg/mL, 95% CI (−2.30, −2.23), p < 0.01, n = 4, 180/180 participants].ConclusionCompared to RAT for KOA, FSN demonstrates superior efficacy in alleviating pain, reducing inflammation, and improving joint dysfunction. Further high-quality studies are needed to determine the long-term efficacy of FSN.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024595903.